Genetic implications of phylogeographical patterns in the conservation of the boreal wetland butterfly Colias palaeno (Pieridae) - Krampl, K.; Čížek, O.; Madeira, P. M.; Ramos, A. A.; Konvička, M. (Martin); Castilho, R.; Schmitt, T. (Biological Journal of the Linnean Society, 2016)
The boreo-montane wetland butterfly species Colias palaeno has a European distribution from the Alps to northern Fennoscandia. Within its European range, the species' populations have shrunk dramatically in recent historical times. Therefore, detailed baseline knowledge of the genetic makeup of the species is pivotal in planning potential conservation strategies. We collected 523 individuals from 21 populations across the entire European range and analyzed nuclear (20 allozyme loci) and mitochondrial (600bp of the cytochrome c oxidase subunit I gene) genetic markers. The markers revealed contrasting levels of genetic diversity and divergence: higher in allozymes and lower in mitochondrial sequences. Five main groups were identified by allozymes: Alps, two Czech groups, Baltic countries, Fennoscandia, and Poland. The haplotype mitochondrial network indicates a recent range expansion. The most parsimonious interpretation for our results is the existence of a continuous Wurm glacial distribution in Central Europe, with secondary disjunction during the Last Glacial Maximum into a south-western and a north-eastern fragment and subsequent moderate differentiation. Both groups present signs of postglacial intermixing in the Czech Republic. However, even a complete extinction in this region would not considerably affect the species' genetic basis, as long as the source populations in the Alps and in northern Europe, comprising the most relevant evolutionary units for conservation, are surviving.